Exploring the relationship between post-contrast acute kidney injury and different baseline creatinine standards: A retrospective cohort study - Ying, Jixiang; Wang, Junren; Ying, Zhiye; Ran, Xingwu; Zeng, Xiaoxi; Chen, Dawei; Gao, Yun; Zhong, Li (Frontiers in Endocrinology, 2023)
Objective: According to previous studies, the incidence of post-contrast acute kidney injury(PC-AKI) in diabetic is far higher than that in the general population. Therefore, we explored the relationship between the incidence of PC-AKI and different baseline serum creatinine (SCr) levels, and determined the relationship between PC-AKI and different types of contrast media (CMs), different doses of CM, and different examination methods in this specific population. Materials and Methods: Patients with diabetes in whom CM was used between 2010 and 2020 at our institution were included. Participants were identified according to the following three schemes: Scheme 1 (n=5911), SCr was detected before and within 72 h after using CM; Scheme 2 (n=2385), SCr was detected within 24 h before and within 24–72 h after using CM; and Scheme 3 (n=81), SCr was detected within 24 h before and within 0–24, 24–48, and 48–72 h after using CM. The incidence of PC-AKI with different types of CM, incidence of PC-AKI on digital subtraction angiography (DSA) and enhanced computed tomography (CT), proportion of PC-AKI with different doses of CM, and baseline SCr at different stages of PC-AKI were compared. Multivariate logistic regression analysis was used to explore risk factors for PC-AKI. Results: A total of 29,081 patients were included in this study. The incidence of PC-AKI in Scheme 3 (22.22%) was higher than those in Schemes 1 (6.19%) and 2 (7.71%). The incidence of PC-AKI on DSA was higher than that on enhanced CT (8.30% vs. 5.80%; P<0.05). The incidence of PC-AKI in the increased-dose CM group was higher than that in the non-increased-dose CM group (7.9% vs. 5.7%; P<0.01). Moreover, there were differences in baseline SCr values at different stages of PC-AKI (P<0.01). Multivariate logistic regression analysis showed that hypertension, chronic kidney disease, heart failure, peripheral vascular disease, metformin, diuretics, and CM dose were risk factors for PC-AKI. Conclusion: The incidence of PC-AKI increased significantly with increasing time requirement and frequency of SCr detection. Moreover, before using CM, we should control the blood pressure and heart failure, stop using metformin and diuretics, and use CMs at the minimum dose to avoid PC-AKI.